Establishing the service evaluation and selection system for emerging culture festival events using the hybrid MCDM technique. Issue 18 (16th September 2020) - Lin, Chia-Li; Chang, Kai-Chih
ABSTRACT: Music festival events are now hosted all over Taiwan and attract thousands of visitors every year, creating a massive need for festival tourism. These music festival events not only invite composers to demonstrate their musical creations. But also they assist many independent bands realizing their musical dreams. This study analyzes how to influence the event image of music festival events for event participants. And it explores how factors that affect the tourist experience and enhance the event image related to this kind of activity. This study used four aspects to build a development strategies map utilizing the DEMATEL technique for the music festival events and establishes the group components of the PCA technique and then adopts the ANP technique to evaluate the aspects/components' weights. Finally, the VIKOR technique was utilized to assess the competitive performance of the music festival events. The research reveals that the PP (package price) and SP (site planning) are primary influencers for music festival events. The event service providers can improve their promotional strategies by the NRM (network relation map) technique. This research provides recommendations for service providers to enhance their equipment plans and service experiences for music festival events.